Pemanfaatan Google Analytics Dan Facebook Ads Sebagai Strategi Pemasaran Digital Bagi UMKM Dan Startup - Ahmad Faqih; Ahmad Rifa'i; Arga Esa Putra; Marfelio Muhammad Fajid (AMMA : Jurnal Pengabdian Masyarakat, 2024)
In the competitive digital era, Micro, Small and Medium Enterprises (MSMEs) and startups are required to adopt data-driven marketing strategies to improve promotional effectiveness and competitiveness. However, many of them still face obstacles in understanding and implementing digital analytics tools such as Google Analytics and advertising platforms such as Facebook Ads. These issues include a lack of understanding of data analytics, difficulties in determining target audiences, as well as budget and resource constraints. This programme aimed to provide practical training and mentoring in the use of both platforms as a solution to improve digital marketing effectiveness. The results showed that 85% of participants experienced increased understanding, and more than 70% successfully implemented more efficient and measurable digital campaigns. In addition to increasing digital engagement and sales conversion, the programme also established a digital marketing community for continued learning. This programme is proven to encourage business independence in managing their digital marketing strategies and contributing to local economic growth.